Antioxidant, Cytotoxic Activities and Total Phenolic Content of Four Indonesian Medicinal Plants - Waras Nurcholis; Bambang Pontjo Priosoeryanto; Edy Djauhari Purwakusumah; Takeshi Katayama; Toshisada Suzuki (Jurnal Kimia Valensi, 2012)
The crude ethanol extracts of four Indonesian medicinal plants namely Curcuma xanthorrhiza Roxb.,Phyllanthus niruri Linn., Andrographis paniculata Ness., and Curcuma aeruginosa Roxb. wereexamined for their antioxidant (radical scavenging) activity using 2, 2-diphenyl-2-picrylhydrazyl(DPPH) free radical and cytotoxicity using brine shrimp lethality test (BSLT). The total phenoliccontent was used the Folin-Ciocalteu method. IC50 values for DPPH radical scavenging activityranged from 14.5 to 178.5 μg/ml, with P. niruri having the lowest value and therefore the mostpotent, and C. aeruginosa having the highest value. LC50 values for BSLT ranged from 210.3 to593.2 μg/ml, with C. xanthorrhiza and A. paniculata having the lowest and highest values,respectively. The total phenolic content of the Indonesian plants ranged from 133.0 ±3.7 to863.3±54.7 mg tannic acid equivalent per 1 g extract, with C. aeruginosa and P. niruri having thelowest and highest values, respectively. A positive correlation between free radical scavengingactivity and the content of phenolic compounds was found in the four of Indonesian medicinal plants.